International Labor Mobility and Child Work in Developing Countries - Anna De Paoli; Mariapia Mendola (Institute for the Study of Labor (IZA), 2014)
This paper investigates the labor market effect of international migration on child work in countries of origin. We use an original cross-country survey dataset, which combines information on international migration with detailed individual-level data on child labor at age 5-14 in a wide range of developing countries. By exploiting both within- and cross-country variation and controlling for country fixed effects, we find a strong empirical regularity about the role of international mobility of workers in reducing child labor in disadvantaged households through changes in the local labor market.
Keywords: F22; F1; J61; 330; international migration; child labor; factor mobility; cross-country survey data